Characterization of Serine Hydrolases Across Clinical Isolates of Commensal Skin Bacteria Staphylococcus epidermidis Using Activity-Based Protein Profiling - Keller, Laura J; Lentz, Christian S; Chen, Y Erin; Metivier, Rebecca J; Weerapana, Eranthie; Fischbach, Michael A; Bogyo, Matthew (ACS infectious diseases, 2020)
The bacterial genus comprises diverse species that colonize the skin as commensals but can also cause infection. Previous work identified a family of serine hydrolases termed fluorophoshonate-binding hydrolases (Fphs) in the pathogenic bacteria , one of which, FphB, functions as a virulence factor. Using a combination of bioinformatics and activity-based protein profiling (ABPP), we identify homologues of these enzymes in the related commensal bacteria . Two of the Fph enzymes were not identified in . Using ABPP, we identified several candidate hydrolases that were not previously identified in that may be functionally related to the Fphs. Interestingly, the activity of the Fphs vary across clinical isolates of . Biochemical characterization of the FphB homologue in (SeFphB) suggests it is a functional homologue of FphB in , but our preliminary studies suggest it may not have a role in colonization . This potential difference in biological function between the Fphs of closely related staphylococcal species may provide mechanisms for specific inhibition of infection without perturbing commensal communities of related bacteria.